The Woman Candidate for the Ontario Legislative Assembly, 1919-1929 - Scollie, Frederick (Ontario History, 2012)
History paints a bleak picture of Ontario women's lack of electoral success after 1919, the year women secured the right to provincial and municipal elective office. This article examines thirteen of twenty-one women who ran unsuccessfully as candidates for the Ontario Legislative Assembly before 1943, especially the twelve who were candidates between 1919-1929, the political success of some of their predecessors elected as school trustees as early as 1892, and the experience of these women with political parties. It tests to what extent the historical record confirms political scientist Sylvia Bashevkin's analysis of women and party politics in English Canada and sociologist Thelma McCormack's theory of male and female dual political cultures.